2010
DOI: 10.4103/0974-2727.66703
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Patterns and Hematological Spectrum in Autoimmune Hemolytic Anemia

Abstract: Background:Autoimmune hemolytic anemia (AIHA) results from red cell destruction due to circulating autoantibodies against red cell membrane antigens. They are classified etiologically into primary and secondary AIHAs. A positive direct antiglobulin test (DAT) is the hallmark of diagnosis for AIHA.Methods and Results:One hundred and seventy-five AIHA cases diagnosed based on positive DAT were included in the study. The cases showed a female predilection (M: F = 1:2.2) and a peak incidence in the third decade. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Few studies have compared the clinical and biochemical differences between primary and secondary wAIHA [61619]. In our population, the only statistically significant difference encountered between these two groups was the correlation of a mixed pattern with secondary wAIHA ( P <0.001).…”
Section: Discussionmentioning
confidence: 74%
“…Few studies have compared the clinical and biochemical differences between primary and secondary wAIHA [61619]. In our population, the only statistically significant difference encountered between these two groups was the correlation of a mixed pattern with secondary wAIHA ( P <0.001).…”
Section: Discussionmentioning
confidence: 74%
“…Similar finding but with different approach, Hirano et al reported that more than 138 IgG molecules per RBC in AIHA patients can render the direct Coombs test distinctly positive (Hirano et al , ). Various reasons have been given to explain Coombs negativity in AIHA (Lin et al , ; Alwar et al , ; Segel & Lichtman, ). Firstly, the number of IgG sensitised red cells may be below the detection threshold by direct Coombs test.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in India have reported the frequency of secondary AIHA as 77% and 29%. (8,9) Baek et al have observed that majority of patients with primary AIHA were found to have SLE during a followup of two years. (10) In the present study, fragmentation hemolysis represented the most frequent form of non-immune acquired hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%